Prostatic urethral lift: A minimally invasive treatment for benign prostatic hyperplasia - Garcia, Cindy (Prostate Int, 2015)
Prostatic urethral lift (PUL) is a minimally invasive procedure for the treatment of lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia. The procedure may be performed under local, spinal, or general anesthesia. The PUL procedure involves the delivery of implants that retract obstructing prostate lobes. Unlike other benign prostatic hyperplasia treatment options including pharmacological therapy, and the current invasive gold-standard transurethral resection of the prostate, the PUL procedure achieves quantifiable improvements in functional outcomes and quality of life, in the absence of major adverse events. Furthermore, improvement in LUTS may be attained while preserving erectile and ejaculatory function. Adverse effects associated with the PUL procedure are mild to moderate, and are transient in nature. The PUL procedure provides an alternative for men seeking treatment for bothersome LUTS, with fewer side-effects.